Methionine restriction provides sex-specific protection against high-fat diet-induced adiposity, peripheral insulin resistance, and neuroinflammation in FGF21-dependent and independent manners in mice - Hannah Lail; Rowan Lawrence; Filipe Pinheiro; Emily Price; Desiree Wanders (PLoS ONE, 2026)
Excessive consumption of high-fat diets is linked to peripheral insulin resistance, neuroinflammation, and obesity. While dietary methionine restriction improves peripheral metabolic health, its effectiveness in attenuating central insulin resistance and neuroinflammation, especially in a sex-dependent manner, remains unclear. This study investigates whether methionine restriction can mitigate high-fat diet-induced alterations in insulin resistance and neuroinflammation in male and female mice and explores the role of endogenous fibroblast growth factor 21 (FGF21) in mediating these effects. We utilized wild-type and Fgf21 knockout ( Fgf21 -/- ) mice to assess the impact of methionine restriction on body composition, insulin sensitivity, central insulin signaling, and neuroinflammation. methionine restriction reduced body weight and adiposity in males, regardless of diet or genotype. In females, methionine restriction reduced weight gain under high-fat diet conditions in both genotypes but had limited effects on female adiposity. Methionine restriction improved insulin sensitivity in WT mice, but this effect was absent in Fgf21 -/- mice, highlighting the importance of FGF21. Likewise, methionine restriction enhanced hepatic insulin signaling in WT males, but not Fgf21 -/- males. In contrast, methionine restriction had minimal impact on insulin signaling in the liver or brain of female mice. Methionine restriction decreased neuroinflammatory gene expression in the hippocampus of males following the high-fat diet, a process dependent on FGF21. These findings demonstrate that methionine restriction confers sex-specific protection against high-fat diet-induced metabolic disturbances, with FGF21 playing a critical role in both peripheral and central insulin sensitivity, particularly in males. Future studies should further elucidate the molecular mechanisms underlying the sex-specific effects of methionine restriction and the role of FGF21 in mediating these responses.